2006
DOI: 10.1007/s10750-006-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Lythrum salicaria and Phragmites australis growth characteristics across a European geographical gradient

Abstract: Plants of Lythrum salicaria and Phragmites australis originating from localities across the European northsouth geographical gradient were cultivated in parallel in an outdoor tub experiment. A strong correlation was found between growth and morphometric characteristics related to plant size (plant height, basal diameter, aboveground-and belowground plant biomass, etc.) and the position of the respective populations along the north-south gradient. Plants of both L. salicaria and P. australis from the southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…The effect of a small sample size is clearly seen in the lack of significant correlations of the measured traits with latitude in the native populations. Significant differences in plant traits with latitude have been conclusively shown for native populations of L. salicaria in Europe (Olsson & Å gren, 2002;Bastlová et al, 2004Bastlová et al, , 2006, and so the univariate results from this study cannot be given much credence. Thus, it would be inappropriate to utilize univariate methods to analyze the results of studies which contained a small number of sample populations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The effect of a small sample size is clearly seen in the lack of significant correlations of the measured traits with latitude in the native populations. Significant differences in plant traits with latitude have been conclusively shown for native populations of L. salicaria in Europe (Olsson & Å gren, 2002;Bastlová et al, 2004Bastlová et al, , 2006, and so the univariate results from this study cannot be given much credence. Thus, it would be inappropriate to utilize univariate methods to analyze the results of studies which contained a small number of sample populations.…”
Section: Discussionmentioning
confidence: 71%
“…In a recent study, Montague et al (2008) found significant differences in time to flowering, plant size at time of flowering, and other life-history characteristics in invasive populations of L. salicaria along a portion of its latitudinal gradient from the eastern part of North America. They concluded that the above differences showed that latitudinal clines had been re-established in this part of the invasive range of the species, probably as a result of adaptation to local climatic conditions, in a way similar to that found for native populations of this species in Europe (Olsson & Å gren, 2002;Bastlová et al, 2004Bastlová et al, , 2006. However, L. salicaria is widespread throughout North America, ranging latitudinally from 30°to 56°N and longitudinally from the Atlantic to the Pacific coasts in both the U.S. and Canada (Stuckey, 1980;Thompson et al, 1987;Edwards et al, 1995).…”
Section: Introductionmentioning
confidence: 59%
“…is a robust perennial wetland grass with a broad ecological amplitude, as evidenced by its cosmopolitan distribution and diversity of habitats, ranging from fresh to brackish and even saline waters (Haslam 1972;Brix 1999;Chambers et al 2003). Large phenotypical, morphological, anatomical, and ecophysiological differences between and within the distinct reed genotypes and lineages have previously been reported Lessmann et al 2001;Bastlova et al 2006;Hansen et al 2007;Eller and Brix 2012;Eller et al 2013Eller et al , 2014Nguyen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigate whether latitudinal clines in lifehistory traits, particularly reproductive phenology, are associated with range expansion in introduced populations of Lythrum salicaria L. (purple loosestrife, Lythraceae), a widespread European invader of North American wetlands first reported on the eastern seaboard of northern USA in 1814 (Thompson et al, 1987). Latitudinal clines in flowering time and associated life-history traits have been demonstrated in two separate regions of the species' native range (Olsson & Å gren, 2002;Bastlová et al, 2004Bastlová et al, , 2006Olsson, 2004), but nothing is known of geographic variation in life history among introduced populations. Although early immigration of L. salicaria probably involved multiple introductions, almost all herbarium specimens (up to 1880) were collected in the north-eastern USA.…”
Section: Introductionmentioning
confidence: 99%